Anti-reflux mucosal ablation (ARMA) as a new treatment for gastroesophageal reflux refractory to proton pump inhibitors: a pilot study - Inoue, Haruhiro; Tanabe, Mayo; de Santiago, Enrique Rodríguez; Abad, Mary Raina Angeli; Shimamura, Yuto; Fujiyoshi, Yusuke; Ueno, Akiko; Sumi, Kazuya; Tomida, Hideomi; Iwaya, Yugo; Ikeda, Haruo; Onimaru, Manabu (Endoscopy International Open, 2020)
Background The incidence of proton pump inhibitor (PPI)-refractory gastroesophageal reflux disease (GERD) has been increasing. While surgical intervention with Laparoscopic Nissen Fundoplication remains the gold standard, less invasive anti-reflux interventions are desired. We have developed a minimally invasive anti-reflux mucosal ablation (ARMA) treatment. Herein, we report its technical details and describe its feasibility, safety, and efficacy in PPI-refractory GERD.Methods We conducted a prospective single-center single-arm interventional trial evaluating the outcome of ARMA in 12 patients with PPI-refractory GERD. GERD-Health Related Quality of Life Questionnaire (GERD-HRQL) evaluation, Frequency Scale for the Symptoms of GERD (FSSG) assessment, and impedance-pH monitoring were performed at baseline and at 2 months post-ARMA.Results A total of 12 patients underwent ARMA with a median follow-up duration of 9 months (range: 6 – 14 months). Median GERD-HRQL score significantly improved from 30.5 to 12 (P = 0.002); median FSSG score significantly improved from 25 to 10.5 (P = 0.002), and median DeMeester score decreased from 33.5 to 2.8 (P = 0.049) at 2 months follow-up. No immediate complications were observed.Conclusion Our pilot study has shown that ARMA, a new endoscopic treatment for PPI-refractory GERD, is simple, safe, and improves GERD-related symptoms and objective acid reflux parameters.